Poverty vs. Nutrition: Measuring (Modeling) Policy Trade-offs - Thurlow, James (2018)
James Thurlow Policy Seminar Advancing Research (and Policy) on Nutrition and Agriculture Feb 22, 2018 - 12:15 pm to 01:45 pm EST